Exposure to SARS-CoV-2 and Infantile Diseases - Kanduc, Darja (Global Medical Genetics, 2023)
Background and Aim Immune response against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in newborns and children after prophylactic immunization is currently a relevant research topic. The present study analyzes the issue by examining the possibility that the anti-SARS-CoV-2 immune responses are not uniquely directed against the virus but can—via molecular mimicry and the consequent cross-reactivity—also hit human proteins involved in infantile diseases.Methods Human proteins that—if altered—associate with infantile disorders were searched for minimal immune pentapeptide determinants shared with SARS-CoV-2 spike glycoprotein (gp). Then, the shared pentapeptides were analyzed for immunologic potential and immunologic imprinting phenomena.Results Comparative sequence analysis shows that: (1) numerous pentapeptides (namely, 54) are common to SARS-CoV-2 spike gp and human proteins that, when altered, are linked to infantile diseases; (2) all the shared peptides have an immunologic potential since they are present in experimentally validated SARS-CoV-2 spike gp-derived epitopes; and (3) many of the shared peptides are also hosted in infectious pathogens to which children can have already been exposed, thus making immunologic imprint phenomena feasible.Conclusion Molecular mimicry and the consequent cross-reactivity can represent the mechanism that connects exposure to SARS-CoV-2 and various pediatric diseases, with a fundamental role of the immunologic memory and the history of the child's infections in determining and specifying the immune response and the pathologic autoimmune sequela.
Keywords: SARS-CoV-2 spike gp; molecular mimicry; peptide sharing; cross-reactivity; immunologic imprinting; autoimmune; infantile diseases